(3GdKbd GdeGfY ef GdMQcI CKfGA Gdfhes - (3CHh MGeO Gdecj Hf eMeO Hf Ydj GdHWGhQj GdTQja GdMSjfj,J (B1354 (3g` s
(3ChdgG (B:s
(3hHYO abO SCdfi HYV GdCUMGH Yf Pdc GdYGQV GdPi bO jYJQV HYV GdfGS ai Gdfhe, ef GdKbd GdeGfY ef GdMQcI hGdcdGe s
(3BNQgG (B:s
(3hgPG JjSQ JbjjOg ai LhGH GdSGFd ai ShjYGJ bdjdI hcGf JbjjOg ai ChGNQ YGe (B1332(3g` s
(3efbhdI Yf fSNI GdeDda YGe (B1336 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B72 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs